Pengaruh Keberfungsian Keluarga Terhadap Resiliensi Akademik Mahasiswa Tingkat Akhir - fredericksen amseke; Nofita Ivana Mira Tade; Marleny Rambu Riada (Ra'ah: Journal of Sociology of Religion, 2024)
Academic resilience is the strength and toughness within an individual to recover from negative emotional experiences. One of the factors of external academic resilience is the functioning of the family to be able to strengthen the academic resilience of final year students to be able to survive the circumstances or situations in completing their final assignments. The aim of this research is to determine the influence of family functioning on the academic resilience of final year students of the Pastoral Counseling study program at the Kupang State Christian Institute. The research data collection tool uses a family functioning scale and an academic resilience scale. The subjects of this research were 60 students in the pastoral counseling study program who were completing their final assignments. The data analysis technique uses simple linear regression analysis. The results of this research prove that family functioning has a positive and significant effect on academic resilience by 53.8%. The higher the role of family functioning, the greater the student's academic resilience in completing the final assignment.